Crescimento e acúmulo de nutrientes em cultivares de gergelim - Ribeiro, Rayanne Maria Paula (2016)
Sesame is considered the oldest oilseed in use by mankind. It is a culture of high complexity Morphophysiological with great variability in growth habit. Knowledge about factors involved in the growth and nutrition of plants allows producers proper planning of culture, contributing to a more efficient use of production area aiming to increase productivity becoming the study of the growth and accumulation of nutrients in the ground sesame seeds, but they are still few studies in the Northeast with culture. The purpose of the research was to evaluate the growth and accumulation of nutrients in sesame cultivars during their development. Two experiments were performed in Horta Didactics at UFERSA Mossoro-RN, from November 2014 to February 2015 and from April to July 2015. The experimental delineation in each experiment was a randomized complete block design with four replications. The treatments were arranged in a split plot where each experimental plot was represented by sesame cultivars: CNPA G2, CNPA G3 and CNPA G4 and the subplots consisted of the collection times, the first being conducted 21 days after sowing and the following at intervals of 14 days (35, 49, 63, 77, 91 and 105 DAS). The growth analysis characteristics evaluated were: plant height, stem diameter, leaf area, dry matter accumulation in leaves, stems, fruits and plant, leaf area index, duration of leaf area, leaf area ratio, rate absolute growth, growth rate cultivation, thousand seed weight, number of fruits per plant and grain yield. In relation to the accumulation of chemical analysis were: nitrogen, phosphorus and potassium. The homogeneity of the variances was made for all variables, except for dry weight of the leaf, making it possible to carry out a joint analysis of the experiments. Independent of the cultivation period, sesame plants presented slow growth until 35 DAS, and for the time I growth intensified up to 91 DAS and for the time II until 77 DAS, where the CNPA G4 revealed higher response regarding the cultivars in two harvest time. The total accumulation of nutrients to the cycle of the final followed the decreasing order of N> K> P in the two growing seasons, where period of increased demand for nutrients occurred between 77 and 105 DAS. In relation to the cultivars, the CNPA G3 had higher accumulations at the time I, while the CNPA G4 at the time II